Leiostyla beatae n. sp. from eastern Georgia (Gastropoda: Lauriidae) - Walther, Frank; Hausdorf, Bernhard (Zootaxa, 2015)
Leiostyla R.T. Lowe, 1852 is a disjunctly distributed pupilloid group of land snails known from the Macaronesian islands, Western Europe, Algeria, Bulgaria, Turkey, the Caucasus region and Iran (Pilsbry 1922–1923; Schileyko 1984; Gittenberger & Pieper 1988; Hausdorf 1990). In the Neogene the genus was more widespread in Central and Western Europe (Pilsbry 1922). Thus, the Caucasus region and the Macaronesian islands, where the highest recent diversity of Leiostyla species is found (Pilsbry 1922–1923), can be considered refugial areas.